A Multidisciplinary Understanding on the Industry (International Journal of Innovative Research in Engineering & Management, 2023)
The distinction between B2B and  "mainstream" advertising reflects the limitations of the  traditional, goods-dominant (G-D) model of commerce  and a value creation paradigm based on the "producer" vs.  "consumer" divide. Customer (S-D) logic expands the  understanding of exchange and value creation by stating  that all social and economic actors participating in  commerce (e.g., corporations, customers, etc.) are service delivering, value-creating organizations; hence, any  transaction may be classified as B2B in this sense. B2B  marketing (along with other sub-disciplines) may be  considered relevant to'mainstream' marketing from this  perspective. This broad, actor-to-actor (A2A)  methodology leads to a dynamic, interconnected, and  systemic approach to value creation. This article looks at  how this system works as a computing architecture and the  steps that need to be taken to turn it into a theoretical  market model influenced by advertisement sub disciplines, marketing programmes, and sciences beyond  of business.
Keywords: Discipline; Economic; Marketing; Perspective; Trade